2011
DOI: 10.5114/aoms.2011.24127
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells promote peripheral nerve repair

Abstract: IntroductionRecent evidence suggests that the implantation of bone marrow-derived mesenchymal stem cells improves peripheral nerve regeneration. In this study we aimed to investigate whether adipose-derived stem cells (ADSCs) can be used for peripheral nerve repair.Material and methodsIn a rat model, nerve regeneration was evaluated across a 15 mm lesion in the sciatic nerve by using an acellular nerve injected with allogenic ADSCs. The walking behaviour of rats was measured by footprint analysis, and electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 21 publications
5
79
0
3
Order By: Relevance
“…36 More recently applied stem cells, such as hair follicle pluripotent stem cells and skin-derived stem cells, are also easily accessible and can transdifferentiate into Schwann cell-like cells as well. 23 Although most studies investigating the use of stem cell to enhance nerve regeneration have expressed enthusiasm and have promoted further research, 25,31 researchers have not compared their own data to other studies, nor has anyone proposed an evaluation protocol that would allow a correct comparison of the results. Therefore, the purpose of this meta-analysis is to summarize the effect of different types of stem cells in animal experimental studies used to enhance regeneration after reconstructing a peripheral nerve injury.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…36 More recently applied stem cells, such as hair follicle pluripotent stem cells and skin-derived stem cells, are also easily accessible and can transdifferentiate into Schwann cell-like cells as well. 23 Although most studies investigating the use of stem cell to enhance nerve regeneration have expressed enthusiasm and have promoted further research, 25,31 researchers have not compared their own data to other studies, nor has anyone proposed an evaluation protocol that would allow a correct comparison of the results. Therefore, the purpose of this meta-analysis is to summarize the effect of different types of stem cells in animal experimental studies used to enhance regeneration after reconstructing a peripheral nerve injury.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…To date, ADSCs have become excellent candidates for research and clinical applications. Many studies have shown that ADSC transplantation efficiently improved almost all symptoms of certain diseases, such as liver fibrosis (Harn et al, 2012), nerve defects (Gu et al, 2012;Liu et al, 2011;Santiago et al, 2009), ischemia (Mazo et al, 2012;Rigol et al, 2010), skeletal muscle injury (Pecanha et al, 2012), passive chronic immune thrombocytopenia (Xiao et al, 2012), and myocardial infarction (Yang et al, 2012) in animals, and systemic sclerosis in humans (Riordan et al, 2009;Scuderi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of myelin protein zero, peripheral myelin protein-22 and myelin basic protein also suggest the retention of myelinating capability [98] . Although some reports have found no difference in outcome between ADSC-filled conduits and cell deplete products [49] , the vast majority of studies show an augmented effect [13,28,29,31,99] . Several studies have shown that ADSCs are at least as effective as autologous SCs [21,45,51] .…”
Section: Bone Marrow Derived Stem Cellsmentioning
confidence: 99%